The Effect of Resin and Bioceramic Sealer on Microleakage After Root Canal Obturation - Yonathan Yonathan; Dina Ratnasari (Indonesian Dental Association, 2020)
Introduction: Microleakage is one of the factors which may cause failure in a root canal treatment by the inadequate obturation. There are two materials that are required to do obturation which are gutta-percha and sealer. Examination of microleakage by bacterial leakage method is more similar to clinical condition. On the other hand, bacteria are smaller than dye solution molecules, so that they will give more sensitive results. Objective: The purpose of this research is to determine the differences between the effect of resin and bioceramic sealer on microleakage. Methods: The subjects were 18 first mandibular premolars which were cut leaving 13 mm of root section and prepared with crown down technique to a size of 30/0.07, then the samples were divided into two groups and were obturated using resin and bioceramic sealer. The microleakage examination was carried out using bacterial leakage method using Enterococcus faecalis. All samples except controls were inoculated with Enterococcus faecalis bacteria on the coronal chamber. Results: Chi-square test showed no significant differences between each group (p> 0.05). The difference that occur is only